ChemInform Abstract: Synthetic Approaches to Asymmetric Phthalocyanines and Their Analogues. Issue 5 (February 2015) - Nemykin, Victor N.; Dudkin, Semyon V.; Dumoulin, Fabienne; Hirel, Catherine; Gurek, Ayse Gul; Ahsen, Vefa
Abstract Review: 283 refs.